Potential use of shellfish waste: a review (Research, Society and Development, 2022)
Brazil is a major producer of bivalve molluscs in Latin America. Malacoculture activity is recognized worldwide as an important alternative for generating jobs, income and food, which has contributed to the establishment of traditional communities in their places of origin in a more sustainable way. However, the high densities of bivalve molluscs produced by cultivation can cause environmental impacts causing imbalances in ecosystems, due to a greater production of solid waste from the shells, which originate from the removal of molluscs from the interior of the shells. The objective of this article is to present a bibliographic review based on the current literature on the morphological structure of the mollusk shell and the possible applications of its residues. The outer shell structure is colored (periostracum), composed of an intermediate layer with compressed aragonite plates with a thickness of about 0.5 µm, embedded in a thin organic matrix and by another calcified layer containing calcite needles of various lengths and diameters., and by a nacreous inner layer that is also calcareous. Clam shells are mainly made up of calcium carbonate (CaCO3). Therefore, shell residues have been used in the manufacture of concrete blocks and pavements with low water absorption and resistance to compression; used as food supplements that help fight and prevent osteoporosis; as a mineral filler in polymers, in the manufacture of ecologically more interesting composite materials with improved mechanical and thermal properties, giving them rigidity and thermal stability.